Risk analysis and risk measures applied to the furniture industry - Brito, Irene (2022)
In this work we show how concepts and methods from actuarial risk theory can be applied to risk analysis in industry. Risk analysis consists in identifying, quantifying and classifying or ordering risks. In the proposed methodology, the risks identified in industrial setting, are modeled by loss random variables. The loss random variables are used to calculate the expected loss, the loss variance and exceedance probabilities permitting risk quantification. In order to classify and order risks, besides measures of uncertainty, risk measures, such as Value-at Risk and Tail-Value-at-Risk (or Expected Shortfall) are determined and, together with risk quantification, the risk levels are analysed. To exemplify this methodology, a case study for risk analysis and classification of occupational accidents in the furniture industry was carried out.